AGRICULTURAL EXTENSION IN ASIA: CONSTRAINTS AND OPTIONS FOR IMPROVEMENT - M. B. Baig; F. Aldosari (Journal of Animal and Plant Sciences, 2013)
Today Extension Services for the many countries of the Asian region are facing numerous newly emerged challenges. The most promising and prominent challenges include: Pluralism, Privatization, Globalization and Market Liberation, World Trade Order (WTO), Information and Communication Technology (ICT), Devolution and Decentralization. Now- a-days, the Extension clienteles have preference for demand driven and participatory approaches. The need for an up-to- date Extension advice to the farmers on farming systems and marketing linkages is becoming increasingly important. In the past, extension systems of the region have not been able to make positive impacts on increasing agricultural production. Due and focused efforts have not been made regarding the transfer of new farming technologies efficiently and effectively. The purpose of this paper is by-fold; firstly to identify and enlist the problems associated with the existing traditional agricultural extension systems of the region and secondly accommodate the newly emerged challenges. It aims at devising suitable recommendations to improve the situation. Prime shortcomings and the major constraints associated with the extension services include: defects in extension organization, insufficient incentives to the extension professionals, lack of sufficient funds and resources, and absence of in-service training facilities. Extension has many approaches and methods at its disposal. However, it is important to carefully tailor the extension methodologies keeping in view perceived needs of a particular country. Since the literacy rate in most of the Asian countries is low, therefore in the situation, television, video and other pictorial means of communication could be useful for delivering and transferring new technologies to the illiterate farmers and less educated rural masses. A vast majority of the poor farmers use farm radio to seek extension advice. However, the complex and complicated messages comprising more technical information through radio should not be disseminated. Yet, the Information and Communication Technology (ICT) can be combined with the other extension methods for making extension more effective.
Keywords: Extension Systems; Constraints; Emerging Challenges; Devolution; Information technology; Improvement Strategies